Effects of Combined Regimens of Gabapentin and Verapamil with Diazepam on Kindled Model of Epilepsy in Mice - Itefaq Hussain Qureshi; Shabana Usman Simjee (Journal of Bahria University Medical and Dental College)
Objective: To compare the in vivo effects of anticonvulsant combined regimens of Gabapentin / Verapamil with diazepam on kindled model of Epilepsy in Mice. Materials and Methods: This experimental study was carried out in Hussain Ebrahim Jamal (H.E.J.) Research Institute of Chemistry, International Center for Chemical and Biological Sciences, University of Karachi, Karachi from May 2009 to July 2011.Gabapentin and Verapamil were used as tested drugs while Diazepam was used as a reference drug. Kindling was produced by repeated administration of Pentylenetetrazole in a dose of 50 mg/kg by subcutaneous route every 48 hours for 20 days. Six doses of Gabapentin from 50mg/kg to 300mg/kg and six doses of Verapamil from 5mg/kg to 30mg/kg in combination regimen were administered by intraperitoneal route. Diazepam was administered by intraperitoneal route in a dose of 7.5mg/kg. Both tested drugs Gabapentin and Verapamil with reference drug Diazepam were administered once daily, however on the day of Pentylenetetrazole treatment the tested and reference drugs were injected 40 minutes before injecting Pentylenetetrazole. The anticonvulsive effects of tested drugs were then compared to reference drug Diazepam. Results: Combination regimens of Gabapentin and Verapamil exhibited synergistic dose dependent anti- seizure effects up to 100%. The maximum dose of combined regimen exhibited antiseizure effects which were superior to the reference drug Diazepam. Conclusion: Combination regimens of Gabapentin and Verapamil showed synergistic effect superior to diazepam on kindled model of epilepsy in mice.